2013
DOI: 10.5539/ijel.v3n3p53
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perceived Teacher Personality on Student Class Evaluations: A Comparison between Japanese Instructors and Native English Speaking Instructors

Abstract: This study explores how university students' perceptions of their classes and instructor personality contribute to their overall rating of the class. The study also investigates whether the students rate Japanese instructors and native English speaking instructors differently. Data was collected using a questionnaire comprised of instructional rating and teacher personality rating sections. The instructional rating section was based on the Instructional Rating Form (Tomasco, 1980), and European Portfolio for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…Mori and Tanabe (2012) conducted a survey with 280 Japanese university students learning English and found a considerable degree of influence of teacher personality on class evaluations. In the subsequent study, Tanabe and Mori (2013) attempted to see whether students' attitudes could differ depending on teacher nationality, Japanese or native English speakers, and found that the teacher personality factor held more weight for the Japanese instructors than native English speaking instructors in terms of overall evaluations of class.…”
Section: Teacher Personality and Setmentioning
confidence: 99%
“…Mori and Tanabe (2012) conducted a survey with 280 Japanese university students learning English and found a considerable degree of influence of teacher personality on class evaluations. In the subsequent study, Tanabe and Mori (2013) attempted to see whether students' attitudes could differ depending on teacher nationality, Japanese or native English speakers, and found that the teacher personality factor held more weight for the Japanese instructors than native English speaking instructors in terms of overall evaluations of class.…”
Section: Teacher Personality and Setmentioning
confidence: 99%
“…Given that large numbers of Japanese students study English with native English speaking teachers (MEXT, 2011;Tanabe & Mori, 2013), who may appear to differ considerably from students in terms of cultural dimensions and value orientations (Hofstede et al, 2010), this study explored potential culture distance that may impact this learning dynamic. Using the Cultural Dimensions of Learning (CDLF) framework, the cultural learning preferences of freshman Japanese university students and Native English speaking Teachers (NESTs) were compared.…”
Section: Discussionmentioning
confidence: 99%
“…The variety of preferences expressed by the participants in this study may have resulted from exposure to multiple instructional environments, and this offers some support for Tran's (2013) claim that pedagogical practices may have a greater impact on learning preferences than culture. The students in this study would likely have been exposed to a variety of instructional approaches as a result of having studied with ALTs from overseas in Japanese junior high and high schools, (MEXT, 2011;Tanabe & Mori, 2013). They were also enrolled in university EFL classes taught by international teachers at the time of this study.…”
Section: Statistically Significant But Small Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of Yoshitaka's research shows that the teacher's personality gives a huge influence on the acceptance of the students, so it is necessary to involve the students in the teacher's personality assessment activities. Students should be a party to assess the personality of teachers with their perceptions [7]. such as Health and Retirement Study (HRS).…”
Section: Literature Reviewmentioning
confidence: 99%